I consensi informati: la relazione con il paziente tra deontologia, legislazione e clinica - Di Agostino, Cecilia (Il sogno della farfalla, 2014)
Within the ambit of the health professions, themes related to Informed Consent, Professional Secrecy and to the legislation that regulates health services to minors concern professional ethics, human and health rights. They also have strong implications on clinical practice in that they affect the relationship with the patient. This is why from the very first contact with the patient and in communicating to him all the facts related to informed consent, the professional must always keep in mind that the clinical relationship is characterized also by unconscious elements. The aim of this present work is to traces the complex Italian laws on this subject and to promote a continuous keeping up to date and stimulate thoughts about the clinical experience which can be shared.